Źródła i konsekwencje wzrostu elastyczności rynku pracy - Łucjan, Izabela (Annales. Etyka w Życiu Gospodarczym, 2016)
The transformation of the modern world of work towards the information society,knowledge society, have a rapid course. These transformations take on a globalcharacter, and the most of their consequences are negative. One of them is to basethe employment process on the flexible solutions. Nowadays, neither the high levelof education, nor the high competences are not enough to give confidence in findingemployment. The contemporary labour market is characterised by unstableness,‘elusiveness’ and, above all, flexibility. The challenge has become a flexible company,which employs only flexible workers within the framework of flexible formsof employment. Despite its universality, the concept of flexibility still remains inconsistentand vaguely defined.